2013
DOI: 10.4161/psb.22510
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging and quantitative monitoring of autophagic flux in tobacco BY-2 cells

Abstract: Autophagy has been shown to play essential roles in the growth, development and survival of eukaryotic cells. However, simple methods for quantification and visualization of autophagic flux remain to be developed in living plant cells. Here, we analyzed the autophagic flux in transgenic tobacco BY-2 cell lines expressing fluorescence-tagged NtATG8a as a marker for autophagosome formation. Under sucrose-starved conditions, the number of punctate signals of YFP-NtATG8a increased, and the fluorescence intensity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
(55 reference statements)
2
26
0
Order By: Relevance
“…Autophagy, a major catabolic pathway in eukaryotic cells, plays a role in the recycling of proteins and metabolites, including lipids, by delivering cytoplasmic components and organelles to degradation compartments such as lysosomes and vacuoles 7 , 8 and is involved in many physiological processes including abiotic and biotic stress responses in plants 9 , 10 . Lipophagy is a type of selective autophagy that has been suggested to contribute to lipid metabolism through the breakdown of intracellular lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy, a major catabolic pathway in eukaryotic cells, plays a role in the recycling of proteins and metabolites, including lipids, by delivering cytoplasmic components and organelles to degradation compartments such as lysosomes and vacuoles 7 , 8 and is involved in many physiological processes including abiotic and biotic stress responses in plants 9 , 10 . Lipophagy is a type of selective autophagy that has been suggested to contribute to lipid metabolism through the breakdown of intracellular lipids.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only limited evidences for this model in plant cells (Rose et al, 2006;Toyooka et al, 2006;Katsiarimpa et al, 2011;Takatsuka et al, 2011;Hanamata et al, 2012). SH3P2-GFP signals were shown to translocate onto the autophagosome membrane upon autophagy induction in Arabidopsis cells (Figures 1B and 2B), indicating its involvement in membrane progression of autophagosome formation.…”
Section: Sh3p2 Reveals the Structure And Dynamics Of Autophagosomesmentioning
confidence: 99%
“…Membrane sources, including the endoplasmic reticulum (ER), mitochondria, ER-mitochondria contact sites, ER-Golgi intermediate compartment, Golgi apparatus, and plasma membrane have been postulated to contribute to autophagosome formation in yeast and/or mammalian cells (Axe et al, 2008;Hayashi-Nishino et al, 2010a, 2010bHailey et al, 2010;Noda et al, 2011;Ohashi and Munro, 2010;Ravikumar et al, 2010;Ge et al, 2013;Hamasaki et al, 2013). In plants, however, most observations of autophagosome-related structures have been based on the classical features of autophagosomes: their isolated double-membrane appearance, enclosed autophagic cargos, and labeling with an autophagosome marker (Rose et al, 2006;Toyooka et al, 2006;Katsiarimpa et al, 2011;Takatsuka et al, 2011;Hanamata et al, 2012). So far, only one electron microscopy (EM) study has shown direct labeling of a double-membrane autophagosome structure in Arabidopsis thaliana with antibodies against the autophagosomal marker ATG8 (Reyes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although autophagy-defi cient mutants of Arabidopsis have been reported to show a normal life cycle, autophagy may also play roles in PCDs in development or stress responses in plants (van Doorn and Woltering 2010 ). A simple easy method to quantitatively analyze autophagic fl uxes has recently been developed in plants (Hanamata et al 2013 ). Such technical advances in combination with genetic analyses may reveal novel aspects of autophagy in PCD in plants.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%